The Newton letter : an interlude - Banville, John, 1945-
A historian, trying to finish a long-overdue book on Isaac Newton, rents a cottage not far by train from Dublin for the summer. All he needs, he thinks, is a few weeks of concentrated work. Why, he must unravel, did Newton break down in 1693? What possessed him to write that strange letter to his friend John Locke? But in the long seeping summer days, old sloth and present reality take over.